The Influence of Liquidity, Dividend Policy and Profitability on Stock Prices in Public Companies in the Industrial Sector Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Sari, Shaila Pratika; Napitupulu, Stephanie Imaylia; Marshanda, Marshanda; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
This study aims to analyze the impact of liquidity, dividend policy, and profitability on stock prices of publicly listed companies in the industrial sector on the Indonesia Stock Exchange during the period of 2020-2023. The method used is multiple linear regression analysis with secondary data sourced from financial statements and stock prices. The results show that the Current Ratio has a negative effect of -0.004, and the Dividend Payout Ratio has a negative effect of -0.123 on stock prices, while Return on Equity has a positive effect of 400.919. The simultaneous test confirms that all three independent variables together have a significant impact on stock prices with an F-statistic value of 1258.590 and a significance level of 0.000. These findings indicate that good management of liquidity, dividend policies, and profitability is crucial for increasing stock prices and attracting investor interest.